Fermentative biohydrogen production by anaerobic, Thermophilic bacterium thermoanaerobacterium aciditolerans Trau DAt isoalted from Vietnam - Yen, Nguyen Thi; Hien, Lai Thuy; Thu Huyen, Nguyen Thi (Academia Journal of Biology, 2015)
Thermoanaerobacterium aciditolerans bacterium Trau DAt isolated in Vietnam had the hydrogen production capability under the anaerobic condition at 55oC. Using glucose, the dark fermentation of strain Trau DAt for hydrogen production was performed in three different scales: the flask scales under the suitable (1) and optimal (2) conditions, and the automatic fermentor system Bio-Flo 110 (3). Under the suitable condition, the strain Trau DAt produced 330 ml volume total gas (L-1) and hydrogen occupied 42.95% of gas total. Under the optimal condition, the maximum volume total gas of 701 ml (L-1) was obtained and hydrogen occupied of 77.2% total volume gas. Based on results of RSM analysis and pH controlled examination, the dark fermentation of strain Trau DAt was performed under automatic fermentor system scale (Bio-Flo 110). 2.64 L total gas (L-1) was obtained by consuming 92.58% glucose and hydrogen volume occupied 94.85% of gas total. The maximum hydrogen yield of strain Trau DAt was 1.63 mol H2 (mol glucose)-1. Obtained results showed the remarkable potentiality of Trau DAt strain in application to the larger fermentation scale for biohydrogen production in Vietnam.